From Ethnic Bourgeoisie to Organic Intellectuals: Speculations on North American Native Leadership - Nagata, Shuichi (Anthropologica, 2022)
A notable feature of native politics in North America in recent decades has been the emergence of Indian associations of varying scales and complexity. These organizations are often led by people whom Rolf Knight has called "ethnic bourgeoisie." This type of lead ership is also found at local band and tribal council levels, and appears to have arisen in response to the force of bureaucratic encapsulation. Problematic aspects of this leadership are explored, and the Gramscian notion of "organic intellectuals" is used to speculate on the direction of changes in this leadership to overcome some of its problems.